Effectiveness of bone expansion, compacting and densification in narrow alveolar crests: a systematic review and a meta-analysis - López-Valverde, Nansi; López-Valverde, Antonio; Blanco, José Antonio (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe treatment of edentulism with dental implants is a common and reliable procedure with high medium- and long-term survival rates. Primary stability in the bone is vitally important to prevent micro-movements at the beginning of healing. However, the main drawback of dental implantology is bone deficiency. To alleviate this situation, clinicians’ resort to surgical techniques that increase bone volume and allow the devices to be placed. Bone expansion, compaction, and densification are used to compact the bone trabeculae, densifying the bone and improving the primary stability and osseointegration of implants. The aim of the study was to evaluate the role of these surgical techniques in deficient alveolar ridges in order to prepare them to receive durable dental implants.MethodsSearches were made of the PubMed/Medline, Embase, Cochrane Central, Dentistry and Oral Sciences Source and Web of Science (WOS) databases and GreyNet International, to identify RCTs, prospective studies, retrospective studies and case series published in English in the last 15 years, which evaluated the efficacy of bone expansion, bone compaction and densification in narrow alveolar ridges and their impact on bone density (BD), alveolar ridge expansion (CE) and implant stability quotient (ISQ). Methodological quality was evaluated using the Joanna Briggs Institute for RCTs (JBI MAStARI) tool and risk of bias using the Cochrane Risk of Bias Tool (RoB2), and meta-analyses were performed using Review Manager 5.4.1 software to calculate effect size and integrate the results of the included studies.ResultsTen of the 2,464 studies examined met the inclusion criteria. The meta-analysis of the parameters analyzed was favorable for the experimental group, indicating that bone expansion, compaction and densification techniques significantly increase DB (−0.71, 95% CI (Confidence Interval) [-1.15 to −0.27], p = 0.002), EC (−1.12, 95% CI [-2.21 to −0.03], p = 0.04) and ISQ (−8.88, 95% CI [-13.85 to −3.91], p = 0.0005), with a high publication bias for CE and ISQ.ConclusionThe techniques of bone expansion, compaction and densification demonstrated their effectiveness in narrow alveolar ridges, although studies are needed to validate the results found.Systematic Review RegistrationIdentifier CRD42025646738.